Efficacy of Early Physical Therapy in Severe Bell's Palsy: A Randomized Controlled Trial. (July 2013) - Nicastri, Maria; Mancini, Patrizia; De Seta, Daniele; Bertoli, GianAntonio; Prosperini, Luca; Toni, Danilo; Inghilleri, Maurizio; Filipo, Roberto
Background . Bell's palsy (BP) is the most frequent form of peripheral palsy of the facial nerve. Prognosis for recovery is good for most patients; in the remaining cases, different grades of residual impairment persist. Physical therapy, in association with drug administration, aims to improve outcomes. Objective . To assess the efficacy of early physical therapy in association with standard drug administration versus pharmacological therapy only, in terms of time to maximum gains and grade of recovery of function, and to examine who will most benefit from rehabilitation. Methods . From June 2008 to May 2010, 232 individuals were evaluated. The 87 patients meeting the eligibility criteria were randomly assigned to the experimental group (prednisone and valacyclovir plus physical therapy, n = 39) or the control group (pharmacological therapy, n = 48) within 10 days of onset. Intention-to-treat analyses were done. Results . The physical therapy had a significant effect on grade ( P = .038) and time ( P = .044) to recovery only in patients presenting with severe facial palsy (House-Brackmann [HB] grade V/VI). No significant differences were found between the study and control groups for outcome of synkinesis. Conclusion . Physical therapy appears to be effective only in the more severe BP (baseline HB grade V/VI), whereas less severe BP (baseline HB grade IV) results in complete spontaneous recovery, regardless of physical therapy.